2004
DOI: 10.1299/jsmec.47.686
|View full text |Cite
|
Sign up to set email alerts
|

Robust Stability Analysis of TS-Fuzzy-Model-Based Control Systems with Both Elemental Parametric Uncertainties and Norm-Bounded Approximation Error

Abstract: This paper discusses the robust stability of Takagi-Sugeno (TS) fuzzy model based control systems. First, it is pointed out that the complex nonlinear control systems with uncertain parameters can be represented as the TS-fuzzy-model-based control systems with both elemental parametric uncertainties and norm-bounded approximation error. Next, a sufficient condition is proposed in terms of linear matrix inequalities (LMIs) for ensuring that the TSfuzzy-model-based control systems with both elemental parametric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In many interesting problems, we only have a small number of uncertain parameters, but these uncertain parameters may enter into many entries of the system and input matrices . Therefore, in this paper, we suppose that the time‐varying parametric uncertain matrices Δ A i ( t ) and Δ B i ( t ) take the forms ΔAi(t)MathClass-rel=falsefalseMathClass-op∑kMathClass-rel=1aϵik(t)Eik and ΔBi(t)MathClass-rel=falsefalseMathClass-op∑kMathClass-rel=1aηik(t)VikMathClass-punc, where ϵ ik ( t ) (falsemml-underlineϵ̲ikϵik(t)trueϵ̄ik, for i = 1,2, … , N and k = 1,2, … , a ) and η ik ( t ) (falsemml-underlineη̲ikηik(t)trueη̄ik, for iMathClass-rel=1MathClass-punc,2MathClass-punc,MathClass-op…MathClass-punc,N and kMathClass-rel=1MathClass-punc,2MathClass-punc,MathClass-op…MathClass-punc,a) are the time‐varying elemental parametric uncertainties, and E ik and V ik ( i = 1,2, … , N and k = 1,2, … , a ) are, respectively, the given n × n and n × p constant matrices which are prescribed a priori to denote the linearly dependent information on the time‐varying elemental parametric uncertainties ϵ ik ( t )'s and η ik ( t )'s, respectively.…”
Section: Problem Statementmentioning
confidence: 99%
“…In many interesting problems, we only have a small number of uncertain parameters, but these uncertain parameters may enter into many entries of the system and input matrices . Therefore, in this paper, we suppose that the time‐varying parametric uncertain matrices Δ A i ( t ) and Δ B i ( t ) take the forms ΔAi(t)MathClass-rel=falsefalseMathClass-op∑kMathClass-rel=1aϵik(t)Eik and ΔBi(t)MathClass-rel=falsefalseMathClass-op∑kMathClass-rel=1aηik(t)VikMathClass-punc, where ϵ ik ( t ) (falsemml-underlineϵ̲ikϵik(t)trueϵ̄ik, for i = 1,2, … , N and k = 1,2, … , a ) and η ik ( t ) (falsemml-underlineη̲ikηik(t)trueη̄ik, for iMathClass-rel=1MathClass-punc,2MathClass-punc,MathClass-op…MathClass-punc,N and kMathClass-rel=1MathClass-punc,2MathClass-punc,MathClass-op…MathClass-punc,a) are the time‐varying elemental parametric uncertainties, and E ik and V ik ( i = 1,2, … , N and k = 1,2, … , a ) are, respectively, the given n × n and n × p constant matrices which are prescribed a priori to denote the linearly dependent information on the time‐varying elemental parametric uncertainties ϵ ik ( t )'s and η ik ( t )'s, respectively.…”
Section: Problem Statementmentioning
confidence: 99%
“…In many interesting problems, we have only a small number of uncertain parameters, but these uncertain parameters may enter into many entries of the system and input matrices [12], [13]. Therefore, in this paper, we suppose that the structured parametric uncertain matrices The resulting TS fuzzy descriptor system with structured parametric uncertainties inferred from Eq.…”
Section: Robust Controllability Analysismentioning
confidence: 99%
“…Furthermore, it is presumed that the estimation error between the T‐S fuzzy model and the nonlinear control system is a norm bounded uncertainty 50,51 . However, Reference 52 has demonstrated that the outcomes are more conservative than that of considering the elemental information of the parametric uncertain matrices. Moreover, the uncertainties in parameter of system have been supposed to fulfill the matching conditions, and the external disturbances should satisfy the norm conditions with defined nonnegative scalars 53,54 .…”
Section: Introductionmentioning
confidence: 99%